Inhibitory control, exploration behaviour and manipulated ecological context are associated with foraging flexibility in the great tit. Issue 2 (24th October 2021) - Coomes, Jenny R.; Davidson, Gabrielle L.; Reichert, Michael S.; Kulahci, Ipek G.; Troisi, Camille A.; Quinn, John L.
Abstract: Organisms are constantly under selection to respond effectively to diverse, sometimes rapid, changes in their environment, but not all individuals are equally plastic in their behaviour. Although cognitive processes and personality are expected to influence individual behavioural plasticity, the effects reported are highly inconsistent, which we hypothesise is because ecological context is usually not considered. We explored how one type of behavioural plasticity, foraging flexibility, was associated with inhibitory control (assayed using a detour‐reaching task) and exploration behaviour in a novel environment (a trait closely linked to the fast–slow personality axis). We investigated how these effects varied across two experimentally manipulated ecological contexts—food value and predation risk. In the first phase of the experiment, we trained great tits Parus major to retrieve high value (preferred) food that was hidden in sand so that this became the familiar food source. In the second phase, we offered them the same familiar hidden food at the same time as a new alternative option that was visible on the surface, which was either high or low value, and under either high or low perceived predation risk. Foraging flexibility was defined as the proportion of choices made during 4‐min trials that were for the new alternative food source. Our assays captured consistent differences among individuals in foraging flexibility. Inhibitory control was associated with foraging flexibility—birds with high inhibitory control were more flexible when the alternative food was of high value, suggesting they inhibited the urge to select the familiar food and instead selected the new food option. Exploration behaviour also predicted flexibility—fast explorers were more flexible, supporting the information‐gathering hypothesis. This tendency was especially strong under high predation risk, suggesting risk aversion also influenced the observed flexibility because fast explorers are risk prone and the new unfamiliar food was perceived to be the risky option. Thus, both behaviours predicted flexibility, and these links were at least partly dependent on ecological conditions. Our results demonstrate that an executive cognitive function (inhibitory control) and a behavioural assay of a well‐known personality axis are both associated with individual variation in the plasticity of a key functional behaviour. That their effects on foraging flexibility were primarily observed as interactions with food value or predation risk treatments also suggest that the population‐level consequences of some behavioural mechanisms may only be revealed across key ecological conditions. Abstract : This work points to the complex nature of the mechanisms underlying behavioural plasticity. It shows that individual foraging flexibility is associated with cognitive and personality measures (inhibitory control and exploration behaviour) simultaneously, in a manner that is sensitive to the precise nature of the changing ecological conditions.